2006
DOI: 10.1103/physrevb.73.233203
|View full text |Cite
|
Sign up to set email alerts
|

Structure and formation mechanism of blue-light-emitting centers in silicon and silica-based nanostructured materials

Abstract: We propose a model of the blue-light-emitting center in silicon and silica-based materials on the basis of the density functional theory calculations. It has been shown that the dehydroxylation reaction involved in the annealing process of surface hydroxyl groups results in the formation of a defect pair consisting of a dioxasilirane, vSi͑O 2 ͒, and a silylene, vSi:, center. The resulting defect pair has the allowed electronic transition energies of ϳ3.5 and ϳ5 eV, in agreement with the peak positions of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
114
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(139 citation statements)
references
References 22 publications
21
114
0
Order By: Relevance
“…This theory has shown that the photoluminescence excitation wavelength of this defect pair is in the range of 240-364nm, which is in agreement with the photoluminescence excitation wavelength of silica gel at 350nm. Based on this we measure the photoluminescence emission wavelength of silica submicron rods and from Fig.3 we can easily see that the silica submicron rods exhibited blue light [18], which is in agreement with the result of the literature. And we can conclude that the blue emission of the obtained silica submicron rods is caused by the surface-associated defects.…”
Section: Fig4 Emission Spectra Of Silica Submicron Rodssupporting
confidence: 79%
“…This theory has shown that the photoluminescence excitation wavelength of this defect pair is in the range of 240-364nm, which is in agreement with the photoluminescence excitation wavelength of silica gel at 350nm. Based on this we measure the photoluminescence emission wavelength of silica submicron rods and from Fig.3 we can easily see that the silica submicron rods exhibited blue light [18], which is in agreement with the result of the literature. And we can conclude that the blue emission of the obtained silica submicron rods is caused by the surface-associated defects.…”
Section: Fig4 Emission Spectra Of Silica Submicron Rodssupporting
confidence: 79%
“…1), 44) similar to the case of oxidized porous silicon. Thus, the blue PL characteristics that were originally found in oxidized porous silicon can also be seen in silica-based nanostructured materials.…”
Section: )supporting
confidence: 49%
“…1,2 On the other hand, blue-green emission is ascribed to surface-related defects, including both C or OH groups adsorbed at the surface of the porous material. [1][2][3][4][5][6] As regards silica-based nanostructered materials, red, green, and blue emissions from silica nanoparticles, mesoporous silica, and silica nanotubes were reported with strong similarities with the spectroscopic features observed in nanoscaled silicon. [7][8][9][10] Since the thickness of the bulk silica walls in nanostructured silica materials ͓ϳ1 nm ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
“…1 Beside the technological interest, the topic is also relevant from a basic research point of view, since the attribution of these optical features to quantum confinement effects or to defect-related mechanisms is still debated. [1][2][3][4][5][6] Concerning porous and nanocrystalline silicon, the emissions in the red to near-infrared region ͑2.1-1.3 eV͒ depend on the dimensions of the Si nanocrystals, providing experimental evidence of the role of the quantum confinement effects. 1,2 On the other hand, blue-green emission is ascribed to surface-related defects, including both C or OH groups adsorbed at the surface of the porous material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation